Zur Effizienz der deutschen Agrarverwaltung; The efficiency of German agricultural administration - Stefan Mann (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– The efficiency of agricultural administration is analysed in this article by costs that arise in a region for administring one hectare farmland or one farm. Variances of these costs between regions can be explained by intra-organisational efficiency on the one hand and by inter-organisational efficiency on the other. Costs for the administration of 131 German regions are empirically estimated. Costs per hectare vary between DM 44 and DM 183. By regression, cost variances can be explained by the area a regional office administers and by the participation of a district office in the system, two important inter-organisational factors. A comparison of services between "cheap" and "expensive" regions does not reveal clear differences.
Keywords: 330; Agrarverwaltung; Verwaltungskosten; Effizienz; Deutschland